Isolasi dan Uji Patogen Bakteri Asam Laktat (BAL) dari Usus Ayam Kampung yang Dipelihara Secara Intensif Di Kefamenanu - Welsiliana; Charles Venirius Lisnahan; Lukas Pardosi (Pro-Life, 2023)
This study aimed to isolate LAB from the intestines of native chickens and to test the ability of LAB activity against pathogenic bacteria. Bacterial isolation was carried out by taking chicken intestines, then diluting up to 102. The results of the dilution were taken 1 ml to be inoculated into MRSA media using the pour plate technique, streak plate technique was used to obtain pure cultures and then incubated at 37˚C for 24 hours. LAB culture testing for pathogenic bacteria was carried out using MHA media containing Escherichia coli cultures, then incubation for 120 hours at 37˚C. Observation parameters included colony shape, colony color, number of LAB colonies, the diameter of the clear zone and LAB colonies. The results showed that the bacteria isolated from the intestines of native chickens were LAB which had around colony shape and were yellowish-white (beige)-milky white. The number of LAB colonies obtained was 3.7 x 105 CFU/ml with the best inhibitory ability of pathogenic bacteria found in USA 3 isolates (1.85 cm clear zone; 0.90 cm colony size) after incubation for 120 hours.